1999
DOI: 10.1097/00003246-199911000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Blind protected specimen brush and bronchoalveolar lavage in ventilated children

Abstract: The results of this study indicate the following: a) nonbronchoscopic PSB and BAL were feasible in a large population of mechanically ventilated children; b) nonbronchoscopic techniques were contributive for diagnosing ventilator-associated pneumonia in children; and c) a combined diagnostic approach, using nonbronchoscopic PSB and BAL, was superior to using either test alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 41 publications
1
44
0
3
Order By: Relevance
“…Minor or moderate bronchial hemorrhage, pneumothorax, and an increase in oxygen or ventilatory requirements, especially in children with poor oxygenation indices, have been previously reported in children after they had undergone BP-BAL. 21 Our study has several limitations. The small size of the tracheostomy tube did not allow us to introduce the flexible bronchoscope alongside the blind protected catheter to detect the BP-BAL sampling sites in all patients.…”
Section: Discussionmentioning
confidence: 91%
“…Minor or moderate bronchial hemorrhage, pneumothorax, and an increase in oxygen or ventilatory requirements, especially in children with poor oxygenation indices, have been previously reported in children after they had undergone BP-BAL. 21 Our study has several limitations. The small size of the tracheostomy tube did not allow us to introduce the flexible bronchoscope alongside the blind protected catheter to detect the BP-BAL sampling sites in all patients.…”
Section: Discussionmentioning
confidence: 91%
“…Labenne et al (60) also investigated the sensitivity and specificity of PSB and BAL in PICU patients with suspected VAP. The gold standards used by those investigators were a positive pleural fluid culture, computed tomography scan with pulmonary abscesses, histopathological evidence, positive lung biopsy (Ͼ10 4 CFU/gram), the same bacteria isolated in blood and endotracheal aspirate without another source, or clinical diagnosis using CDC guidelines established independently by two investigators blinded to PSB/BAL culture results.…”
Section: Invasive Testing In Childrenmentioning
confidence: 99%
“…The safety of the NB-BAL in children has also been determined by several studies; few adverse experiences (n ϭ 18) have been reported (12,42,60,66,79). The types of adverse events were sustained oxygen desaturation requiring increased ventilatory support (n ϭ 11), pneumothorax (n ϭ 4), hypotension (n ϭ 2), and significant increase in intracranial pressure (n ϭ 1).…”
Section: Invasive Testing In Childrenmentioning
confidence: 99%
“…[45] BAL and PSB, both techniques are quite safe, having minor complication such as minimal bronchial hemorrhage, a moderate increase in oxygen and transient fever also reported. [46] Due to the smaller diameter of ETT in neonates, unfortunately PSB and Bronchoscopic BAL cannot be performed in neonates so in the neonates Blind-protected BAL seems to be the best choice for reliable sampling. [47] Antimicrobial susceptibility pattern in our reviewed articles Antimicrobial susceptibility varies significantly according to their use in the hospital in a one region and in the different department of the same hospital.…”
Section: Bed Of Head Elevation and Lateral Positionmentioning
confidence: 99%